Sleep Quality and its Predictors in Brazilian Marines - Portugal, Guillermo Brito; Ferreira, Fabrícia Geralda; Costa, Carlos Magno Amaral; Damasceno, Vinicius de Oliveira; Doimo, Leonice Aparecida (Sleep Science, 2024)
Objectives The objective of this study was to evaluate the quality of sleep and its associated factors in marines (Fuzileiros Navais - FN) of the Brazilian Navy.Material and Methods The participants included 1,248 military personnel who responded remotely to the following instruments: anamnesis, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, International Physical Activity Questionnaire, Eating Habits Scale, and the K10 Questionnaire. Anthropometric information was obtained from a database. Subgroup analysis (good x poor sleep) and regression analysis were performed to verify the factors associated with poor sleep quality.Results A total of 74.12% of the military were characterized by poor sleep quality. There were differences between sleep quality and sociodemographic, behavioral, and professional factors. Age, being an Officer, and physical activity were protective factors, while living with young children, having more energy in the evening, daytime sleepiness, having problems at work, distress, and regular eating habits were predisposing to poor sleep.Discussion Marines of the Brazilian Navy have a high prevalence of poor sleep quality associated with personal, family, and occupational factors as contributors to the problem, indicating the need to develop health actions that favor good sleep hygiene in these professionals.
Keywords: inadequate sleep; armed forces; fatigue; operational capacity; military personnel; national security